THE UTILIZATION OF ICT IN TEACHING AND LEARNING ACTIVITIES BY TEACHERS OF SMK DAR EL HIKMAH BOARDING SCHOOL PEKANBARU - Pahrozi Ahmad; Hadriana Hadriana; Marzuki Marzuki (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This descriptive study aims to discuss to what extent the teachers utilize ICT in teaching and learning activities, as teaching media and learning resources as well as the obstacles faced by teachers while utilizing ICT. The population of this study was the teachers of SMK Dar El Hikmah Boarding School selected by using total sampling technique (n: 20). Data were gathered by distributing a set of questionnaire designed in the form of five points of the Likert scale. The data were analysed using Microsoft Excel 2010. Based on the data analysis, it can be concluded the utilization of ICT in teaching and learning activities in general was in high level category, with the mean of 3.6. Specifically, the utilization of ICT in teaching and learning process was in high category level, and the utilization of ICT as teaching media and learning resources was in mediocre category level, with the mean score of 3.18. Obstacles related to availability of facilities and infrastructures were faced by the teachers and some suggestions to overcome the problems are given in this research.Keywords: Utilization, ICT, teaching media, learning resources.